Characterization of crtRB1 Gene Polymorphism and β-Carotene Content in Maize Landraces Originated From North Eastern Himalayan Region (NEHR) of India - Natesan, Senthil; Singh, Thangjam Surchandra; Duraisamy, Thirusenduraselvi; Chandrasekharan, Neelima; Chandran, Sarankumar; Adhimoolam, Karthikeyan; Muniyandi, Samuel Jeberson; Sampathrajan, Vellaikumar; Kalipatty Nalliappan, Ganesan; Muthurajan, Raveendran; Meitei, Laishram Joykumar (Frontiers in Sustainable Food Systems, 2020)
Micronutrient malnutrition or hidden hunger affects a large population in developing and developed countries. One of the major micronutrient deficiencies is vitamin A, which causes several major disorders such as growth retardation, blindness, and increased susceptibility to infectious disease. Maize has been shown for great natural variation for provitamin A carotenoids and it is a promising crop for provitamin A biofortification. crtRB1 (β-carotene hydroxylase 1) gene is responsible for enhancing β-carotene content in maize. DNA marker linked to the crtRB1 gene had a considerable effect on enhancing β-carotene content that has been identified previously. In India, the North-East Himalayan region (NEHR) is the center of maize diversity, maize landraces from this area have good agronomic characters and well-adapted to stress environments. However, no prior knowledge about the existence of the crtRB1 gene and that of the β-carotene content in NEHR maize landraces is available. Hence, the goal of this study was to characterize the crtRB1 gene polymorphism and β-carotene content in NEHR maize landraces using gene-specific marker (crtRB1 3'TE) and high-performance liquid chromatography (HPLC). We screened 26 maize landraces using crtRB1 3'TE marker and found that all the maize landraces to be either homozygous to the unfavorable allele or heterozygous (both favorable and unfavorable alleles) but no landraces were homozygous for favorable allele. On the other hand, HPLC analysis showed that the β-carotene content in the heterozygous allele type of landraces varied from 1.36 to 4.40 μg/g while unfavorable homozygous allele type landraces varied from 0.33 to 0.94 μg/g. It was found that the landraces CAU-M66 and CAU-M16 possess the highest amount of β-carotene content (4.40 and 4.26 μg/g) and had the crtRB1 favorable allele in heterozygous condition among the 26 maize landraces studied. This is the first study that disclosed the crtRB1 gene polymorphism and the β-carotene content in NEHR maize landraces. The newly identified β-carotene-rich maize landraces can be effectively utilized in the breeding programs to enhance the β-carotene content in maize.